2018
DOI: 10.1101/389445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and efficient C-terminal labeling of nanobodies for DNA-PAINT

Abstract: Single molecule localization-based approaches to superresolution microscopy (SMLM) create images that resolve features smaller than the diffraction limit of light by rendering them from the sequentially measured positions of thousands of individual molecules. New SMLM approaches based on the transient binding of very bright dyes via DNA-DNA interaction (DNA-PAINT) allow the resolution of dyes only a few nanometers apart in vitro. This imaging of cellular structures requires the specific association of dyes to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…It has been demonstrated that small camelid single domain antibodies or nanobodies (15 kDa and ~3 nm in length) have the capacity to increase the accuracy of super-resolution microscopy for mapping POIs in a cellular context[15], [42]. Recently, nanobodies have been coupled to docking oligos to perform DNA-PAINT [25]. Unfortunately, only few nanobodies are currently available that work efficiently in immunoassay applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that small camelid single domain antibodies or nanobodies (15 kDa and ~3 nm in length) have the capacity to increase the accuracy of super-resolution microscopy for mapping POIs in a cellular context[15], [42]. Recently, nanobodies have been coupled to docking oligos to perform DNA-PAINT [25]. Unfortunately, only few nanobodies are currently available that work efficiently in immunoassay applications.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant production of the variable domain of these hcAbs result in a functional nanobody with only 2-3 nm size[24]. Recently, a significant improvement in spatial resolution, as compared to conventional antibody immunofluorescence, was demonstrated by using nanobodies for labeling[12], [25]. In addition to their small size, high specificity, and monovalent binding affinities, which make them an ideal tool for microscopy, the recombinant nature of nanobodies endows them with a great flexibility and allows introducing all types of modifications in a precise manner.…”
Section: Introductionmentioning
confidence: 99%
“…Stably transfected GPI-GFP CV-1 cells were maintained with 50 μg ml −1 Geniticin (ThermoFisher Scientific) supplementing the culture medium. For transient transfection, CV-1 cells at 70-100% confluency were electroporated with the Neon 39 were recombinantly produced 40 and labeled. For the labeling reaction 41 , α-Biotin-ω-(succinimidyl propionate)-24(ethylene glycol) (Iris Biotech) was added to the nanobody at twofold molar excess.…”
Section: Methodsmentioning
confidence: 99%
“…Nanobodies have also been generated to a variety of proteins, including tubulin (Mikhaylova et al. , 2015), to allow direct rather than indirect labeling of microtubules and have been used successfully in SMLM approaches, including DNA PAINT (Fabricius et al. , 2018; Sograte-Idrissi et al.…”
Section: Nanobodies: Alternatives To the Traditional Dual Antibody Lamentioning
confidence: 99%